2000
DOI: 10.1007/s102110000016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological and social challenges in different seasons on fecal testosterone and corticosterone in male domestic geese ( Anser domesticus )

Abstract: We investigated the reliability of the non-invasive approach of measuring steroid hormones from feces in the domestic goose (Anser domesticus), a mainly herbivorous bird with a short gut passage time (2-3 h). Groups of eight outdoor-housed male domestic geese were subjected to three different experiments, injection of either GnRH analogue or ACTH, or "social stimulation" by confrontation with two alien males or females. These experiments were replicated in three different seasons, in spring, during peak reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
3
36
0
3
Order By: Relevance
“…However, in agreement with other studies (Bishop and Hall 1991;Cockrem and Rounce 1994;Palme et al 1996), experiments with domestic geese showed deterministic relationships between plasma steroids and metabolites in the faeces (Hirschenhauser et al 2000a;Kotrschal et al 2000). Therefore, we are confident that our faecal BM and TM levels are representative for plasma corticosterone and T within 2-3 h before defecation.…”
Section: Data Collectionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in agreement with other studies (Bishop and Hall 1991;Cockrem and Rounce 1994;Palme et al 1996), experiments with domestic geese showed deterministic relationships between plasma steroids and metabolites in the faeces (Hirschenhauser et al 2000a;Kotrschal et al 2000). Therefore, we are confident that our faecal BM and TM levels are representative for plasma corticosterone and T within 2-3 h before defecation.…”
Section: Data Collectionsupporting
confidence: 92%
“…The system was probably saturated at the receptors' level and additional T did not produce any further effect (Hutchison 1976;Beletsky et al 1990;Groothuis and Meeuwissen 1992). This is even more remarkable, as steroid excretion seems to be more efficient in spring than in autumn (Kotrschal et al 2000). We assume that there may also have been more carrier protein, which could have buffered additional T and would have made circulating T inert to inactivation and excretion.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In group-living animals, social interactions may have pronounced effects on individuals' subsequent behaviour (de Waal & Yoshihara 1983;Black & Owen 1989;Briffa & Elwood 2001) and physiology ( Hack 1997;Otten et al 1997;Kotrschal et al 2000;Briffa & Elwood 2005). Social interactions affect not only individuals actively involved but also individuals that observe an interaction (bystanders).…”
Section: Introductionmentioning
confidence: 99%
“…One week before and 1 week after the nestlings were placed together, fecal samples were collected daily from individuals to determine excreted corticosterone metabolites by enzyme-immunoassay (EIA). Corticosterone metabolites were analyzed by EIA, as described by Kotrschal et al [1998] and evaluated by Hirschenhauser et al [2000] and Kotrschal et al [2000].…”
Section: Data Collection and Analysismentioning
confidence: 99%